Release film for ceramic green sheet manufacturing process
The release film with a melamine resin, epoxy resin, and polyorganosiloxane composition addresses weak adhesion between ceramic green sheets, improving the manufacturing process by enhancing adhesive strength and reducing defects in laminated ceramic products.
Patent Information
- Application Number
- JP2022508122
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-17
- Filing Date
- 2021-02-04
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-02-04
AI Technical Summary
The adhesive force between ceramic green sheets is weak during lamination, leading to defects such as misalignment, poor cutting, decreased positional accuracy of electrodes, and delamination in laminated ceramic products.
A release film for ceramic green sheets is developed, comprising a base material with a release agent layer formed from a composition containing melamine resin, epoxy resin, and polyorganosiloxane, which enhances adhesive strength and ensures appropriate peeling force without cracking.
The release film improves the adhesive strength between ceramic green sheets, reducing defects and enhancing the reliability of laminated ceramic products by preventing misalignment and delamination.
Smart Images

Figure 0007617080000001 
Figure 0007617080000002 
Figure 0007617080000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a release film used in the process of producing a ceramic green sheet. [Background technology]
[0002] Conventionally, multilayer ceramic products such as multilayer ceramic capacitors and multilayer ceramic substrates have been produced by forming ceramic green sheets, stacking a plurality of the resulting ceramic green sheets, and firing the stacked sheets.
[0003] The ceramic green sheet is formed by coating a ceramic slurry containing ceramic materials such as barium titanate and titanium oxide on a release film. The release film is required to have releasability that allows the release film to be peeled off from the thin ceramic green sheet formed on the release film with an appropriate peeling force without cracking, breaking, or the like.
[0004] As an example of the above-mentioned release film, Patent Document 1 discloses a release film that includes a substrate and a release agent layer provided on one side of the substrate, the release agent layer being formed by curing a release agent composition containing a melamine resin and a polyorganosiloxane. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-105092 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, when manufacturing a multilayer ceramic product, the adhesive strength between the ceramic green sheets is sometimes weak and they do not adhere well when multiple ceramic green sheets are laminated and pressed together. When such poor adhesion occurs, there are problems such as defective cutting due to misalignment of the adhesive surfaces, reduced positional accuracy of electrodes, and delamination after firing the laminate, which reduces the reliability of the multilayer ceramic product.
[0007] An object of the present invention is to provide a release film for use in a ceramic green sheet production process, which enables the production of ceramic green sheets having high adhesive strength between the ceramic green sheets during the lamination process of the ceramic green sheets. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, firstly, the present invention provides a release film for use in a ceramic green sheet production process, comprising a substrate and a release agent layer provided on one side of the substrate, characterized in that the release agent layer is formed from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane (Invention 1).
[0009] In the above invention (Invention 1), the release agent layer is formed from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane, and therefore the adhesive strength between the ceramic green sheets produced using the release film can be increased during the lamination process of the ceramic green sheets.
[0010] In the above invention (Invention 1), the mass ratio of the content of the melamine resin to the content of the epoxy resin in the release agent composition is preferably 99:1 to 30:70 (Invention 2).
[0011] In the above inventions (Inventions 1 and 2), it is preferable that the polyorganosiloxane has at least one hydroxyl group in one molecule (Invention 3).
[0012] In the above inventions (Inventions 1 to 3), the weight average molecular weight of the polyorganosiloxane is preferably 500 or more and 10,000 or less (Invention 4).
[0013] In the above inventions (Inventions 1 to 4), the content of the polyorganosiloxane in the release agent composition is preferably 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the total value of the content of the melamine resin and the content of the epoxy resin (Invention 5).
[0014] In the above inventions (Inventions 1 to 5), the melamine resin is represented by the following general formula (a): [ka] (In the formula, X represents -H, -CH2-OH, or -CH2-OR, and may be the same or different. R represents an alkyl group having 1 to 8 carbon atoms, and may be the same or different. At least one X is -CH2-OH or -CH2-OR.) or a polynuclear compound formed by condensing two or more of the above compounds (Invention 6).
[0015] In the above inventions (Inventions 1 to 6), the weight average molecular weight of the melamine resin is preferably 100 or more and 1000 or less (Invention 7).
[0016] In the above inventions (Inventions 1 to 7), it is preferable that the stripping agent composition contains a catalyst (Invention 8). Effect of the Invention
[0017] According to the release film for use in the ceramic green sheet manufacturing process of the present invention, ceramic green sheets having high adhesive strength between the ceramic green sheets during the lamination process can be manufactured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described. The release film for the ceramic green sheet manufacturing process according to this embodiment (hereinafter sometimes simply referred to as "release film") is configured to include a substrate and a release agent layer provided on one side of the substrate. The release agent layer may be directly laminated on one side of the substrate, or may be laminated on one side of the substrate via another layer.
[0019] 1. Components that make up the release film for the ceramic green sheet manufacturing process (1) Base material The substrate in this embodiment is not particularly limited as long as it can be laminated with a release agent layer. Examples of such substrates include films made of polyesters such as polyethylene terephthalate and polyethylene naphthalate, polyolefins such as polypropylene and polymethylpentene, polycarbonate, and plastics such as polyvinyl acetate, and may be a single layer or a multilayer of two or more layers of the same or different types. Among these, polyester films are preferred, and polyethylene terephthalate films are particularly preferred, and biaxially oriented polyethylene terephthalate films are even more preferred. Since polyethylene terephthalate films have high mechanical strength and excellent solvent resistance, they can achieve stable productivity regardless of the scale of processing and use. Furthermore, by performing antistatic treatment on the polyethylene terephthalate film, it is possible to prevent ignition due to static electricity when applying a ceramic slurry using an organic solvent, and to enhance the effect of preventing coating defects and the like.
[0020] The substrate may contain a filler. When the substrate is multi-layered, the filler may be contained in at least one layer on the surface side.
[0021] In addition, in order to improve the adhesion of the substrate to the release agent layer provided on the surface, one or both sides of the substrate may be subjected to a surface treatment such as an oxidation method or a roughening method, or a primer treatment, if desired. Examples of the oxidation method include corona discharge treatment, plasma discharge treatment, chromium oxidation treatment (wet), flame treatment, hot air treatment, ozone treatment, and ultraviolet irradiation treatment, and examples of the roughening method include sandblasting and thermal spraying treatment. These surface treatment methods are appropriately selected depending on the type of substrate film, but generally, corona discharge treatment is preferably used in terms of effectiveness and operability.
[0022] The thickness of the substrate is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 125 μm or less.
[0023] (2) Release layer The release agent layer in this embodiment is formed from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane.
[0024] According to the release film of this embodiment, the release agent layer is formed from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane, and therefore, the adhesive strength between the ceramic green sheets produced using the release film can be increased during the lamination process of the ceramic green sheets.
[0025] In addition, in the release film of this embodiment, since the release agent composition for forming the release agent layer contains polyorganosiloxane, the surface free energy of the release agent layer on the release surface is appropriately reduced. Furthermore, since the release agent composition contains melamine resin and epoxy resin, the release agent composition can be sufficiently cured by heating (and the presence of a catalyst), and the formed release agent layer has sufficient elasticity. As a result, the peeling force when peeling the release film from the ceramic green sheet formed on the release surface of the release film is appropriately reduced, and good releasability is achieved.
[0026] Generally, the term "melamine resin" refers to a mixture containing multiple types of melamine compounds and / or polynuclear compounds formed by condensation of the melamine compounds. In this specification, the term "melamine resin" refers to the above mixture or an aggregate of one type of melamine compound. Furthermore, in this specification, the cured melamine resin is referred to as a "melamine cured product."
[0027] In addition, in this specification, the term "epoxy resin" refers to a compound having one or more epoxy groups in the molecule, and includes both polymerized and non-polymerized compounds.
[0028] (2-1) Melamine resin The melamine resin is not particularly limited as long as it can form a melamine cured product. In particular, the melamine resin preferably contains a compound represented by the following general formula (a). [ka]
[0029] In formula (a), X represents -H, -CH2-OH, or -CH2-OR. These groups constitute reactive groups in the condensation reaction between melamine compounds, or with the hydroxyl group of polyorganosiloxane, or with the hydroxyl group generated by ring-opening of the epoxy group of epoxy resin. Specifically, the -NH group formed when X becomes H can undergo a condensation reaction with the -N-CH2-OH group and the -N-CH2-R group. In addition, the -N-CH2-OH group formed when X becomes -CH2-OH and the -N-CH2-R group formed when X becomes -CH2-R can both undergo a condensation reaction with the -NH group, the -N-CH2-OH group, and the -N-CH2-R group. In addition, the groups represented by -CH2-OH and -CH2-OR constitute reactive groups that contribute to the condensation reaction between the hydroxyl group of the polyorganosiloxane or the hydroxyl group generated by ring-opening of the epoxy group of the epoxy resin and the melamine compound. In formula (a), it is preferable that all Xs are not -H, and specifically, it is preferable that at least one X is -CH2-OH or -CH2-OR.
[0030] In the group represented by -CH2-OR, R represents an alkyl group having 1 to 8 carbon atoms. The number of carbon atoms is preferably 1 to 4, and particularly preferably 1 to 2. Examples of the alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, and an octyl group, and a methyl group is particularly preferred.
[0031] The X's may be the same or different, and the R's may be the same or different.
[0032] From the viewpoint of excellent efficiency of the above-mentioned condensation reaction, the number of X which becomes -H in the formula (a) is preferably 2 or less, particularly preferably 1 or less, and further preferably 0. A preferred example of a melamine compound in which the number of X which becomes -H is 0 is hexamethoxymethylmelamine in which all X are -CH2-O-CH3.
[0033] The melamine resin may contain a polynuclear compound formed by condensing 2 to 10 compounds represented by the above formula (a), or may contain a polynuclear compound formed by condensing 2 to 8 compounds, or may further contain a polynuclear compound formed by condensing 2 to 5 compounds.
[0034] The weight average molecular weight of the melamine resin is preferably 1000 or less, particularly preferably 900 or less, and more preferably 800 or less. When the weight average molecular weight of the melamine resin is 1000 or less, the curability of the release agent composition is more excellent, and it is easy to form a release agent layer having sufficient coating strength. As a result, it is possible to achieve better release properties. On the other hand, the weight average molecular weight of the melamine resin is preferably 100 or more, particularly preferably 200 or more, and more preferably 300 or more. When the weight average molecular weight of the melamine resin is 100 or more, the reaction rate of the above-mentioned condensation reaction is stable, and it is easy to form a release surface with excellent surface condition. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) method in terms of standard polystyrene.
[0035] (2-2) Epoxy resin In this embodiment, the epoxy resin undergoes ring-opening of the epoxy group in the presence of a catalyst, particularly an acid catalyst, to polymerize the epoxy compounds with each other, or undergoes a condensation reaction between the hydroxyl group generated by ring-opening of the epoxy group of the epoxy resin and the melamine compound to bond. The epoxy resin in this embodiment is a compound having one or more epoxy groups in the molecule, and preferably has two or more epoxy groups in the molecule.
[0036] As such an epoxy resin, various known epoxy resins can be used, and are not particularly limited. Examples of the epoxy resin include biphenyl group-containing epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, brominated bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, biphenyl type epoxy resins, urethane modified epoxy resins, rubber modified epoxy resins, alkylene glycol type epoxy resins such as polyalkylene glycol type, bifunctional glycidyl ether type epoxy resins such as epoxy resins having a naphthalene ring and epoxy resins having a fluorene group; phenol novolac Examples of the epoxy resin include polyfunctional glycidyl ether type epoxy resins such as glycidyl ether type epoxy resins, orthocresol novolac type epoxy resins, trishydroxyphenylmethane type epoxy resins, and tetraphenylolethane type epoxy resins; glycidyl ester type epoxy resins of synthetic fatty acids such as dimer acid; aromatic epoxy resins having glycidylamino groups such as N,N,N',N'-tetraglycidyldiaminodiphenylmethane (TGDDM), tetraglycidyl-m-xylylenediamine, triglycidyl-p-aminophenol, and N,N-diglycidylaniline; and epoxy resins having tricyclodecane rings. As the epoxy resin, one type may be used alone, or two or more types may be used in combination.
[0037] The rubber-modified epoxy resin can be produced by reacting a rubber component with the epoxy group in the epoxy resin. The rubber component is not particularly limited, but examples thereof include butadiene rubber, acrylic rubber, silicone rubber, butyl rubber, olefin rubber, styrene rubber, isoprene rubber, nitrile rubber, styrene-butadiene rubber, and ethylene-propylene rubber. The functional group of the rubber component may be amino-modified, hydroxyl-modified, or carboxyl-modified. The epoxy resin used in producing the rubber-modified epoxy resin is not particularly limited, and any conventionally known epoxy resin may be used.
[0038] The epoxy equivalent of the epoxy resin is preferably 50 g / eq or more, particularly preferably 80 g / eq or more, and more preferably 100 g / eq or more. The epoxy equivalent is preferably 5000 g / eq or less, particularly preferably 2000 g / eq or less, and more preferably 1000 g / eq or less. When the epoxy equivalent of the epoxy resin is within the above range, the adhesive strength between the ceramic green sheets becomes higher. In this specification, the epoxy equivalent is a value measured in accordance with JIS K7236.
[0039] The weight average molecular weight (Mw) of the epoxy resin is preferably 100 or more, particularly preferably 200 or more, and more preferably 300 or more. The weight average molecular weight is preferably 50,000 or less, particularly preferably 30,000 or less, and more preferably 20,000 or less. When the weight average molecular weight of the epoxy resin is in the above range, the adhesive strength between the ceramic green sheets is higher.
[0040] In the release agent composition of the present embodiment, the mass ratio of the melamine resin content to the epoxy resin content is preferably 99:1 to 30:70, particularly preferably 98:2 to 40:60, and further preferably 95:5 to 50:50. When the mass ratio of the melamine resin content to the epoxy resin content is within the above range, the adhesive strength between the ceramic green sheets becomes higher. In addition, the ceramic green sheet formed on the release surface of the release film has excellent releasability when being peeled from the release film.
[0041] (2-3) Polyorganosiloxane The polyorganosiloxane is not particularly limited as long as it can impart the desired releasability to the release agent layer. In the release film according to the present embodiment, the polyorganosiloxane preferably has at least one hydroxyl group in one molecule. By the polyorganosiloxane having a hydroxyl group, the polyorganosiloxane can be chemically fixed in the cured product by condensation reaction with the melamine resin, and as a result, it becomes easy to suppress the migration of the polyorganosiloxane from the release agent layer to the ceramic green sheet.
[0042] The structure of the polyorganosiloxane other than the hydroxyl group is not particularly limited as long as it does not inhibit the above-mentioned releasability and the condensation reaction with the melamine resin. As the polyorganosiloxane, a polymer of a silicon-containing compound represented by the following general formula (b) can be used. [ka]
[0043] In formula (b), m is an integer of 1 or more. 1 ~R 8 each independently represents a hydroxyl group, an organic group (including an organic group having a hydroxyl group), or a group other than these groups. 1 ~R 8 When at least one of R is a hydroxyl group or an organic group having a hydroxyl group, R 3 ~R 8 It is preferable that at least one of the above groups is one of the above groups. That is, when the polyorganosiloxane has a hydroxyl group or an organic group having a hydroxyl group, the group is preferably present at the end of the polyorganosiloxane. The presence of a hydroxyl group at the end makes it easier for the polyorganosiloxane to undergo a condensation reaction with the melamine resin, and the migration of the polyorganosiloxane is effectively suppressed.
[0044] Examples of the organic group include polyester groups and polyether groups, and in particular, the polyorganosiloxane in this embodiment preferably has at least one of polyester groups and polyether groups. The polyorganosiloxane has at least one of polyester groups and polyether groups, so that the polyorganosiloxane and the melamine resin are easily mixed well in the release agent composition, and the extreme phase separation of these during curing is suppressed. This allows the condensation reaction between the polyorganosiloxane and the melamine resin and / or epoxy resin as described above to proceed well, and the migration of the polyorganosiloxane is also effectively suppressed. In this specification, the "organic group" does not include the alkyl group described below.
[0045] Examples of groups other than hydroxyl groups and organic groups (including organic groups having a hydroxyl group) include alkyl groups having 1 to 12 carbon atoms. Examples of alkyl groups having 1 to 12 carbon atoms include methyl groups, ethyl groups, propyl groups, butyl groups, pentyl groups, hexyl groups, and octyl groups, with methyl groups being particularly preferred.
[0046] R 1 ~R 8 may be the same or different. 1 and R 2 If there are multiple, R 1 and R 2 may be the same or different.
[0047] The weight average molecular weight of the polyorganosiloxane is preferably 10000 or less, particularly preferably 8000 or less, and more preferably 5000 or less. On the other hand, the weight average molecular weight of the polyorganosiloxane is preferably 500 or more, particularly preferably 700 or more, and more preferably 1000 or more. When the weight average molecular weight of the polyorganosiloxane is in the above range, the compatibility of the polyorganosiloxane with the melamine resin and the epoxy resin becomes better, and the peeling force when peeling the release film from the ceramic green sheet formed on the release surface of the release film can be controlled to an appropriate magnitude.
[0048] The content of polyorganosiloxane in the release agent composition is preferably 1 part by mass or more, particularly preferably 3 parts by mass or more, and more preferably 5 parts by mass or more, relative to 100 parts by mass of the total value of the melamine resin content and the epoxy resin content. The content of polyorganosiloxane is preferably 50 parts by mass or less, particularly preferably 40 parts by mass or less, and more preferably 30 parts by mass or less, relative to 100 parts by mass of the total value of the melamine resin content and the epoxy resin content. By having the content of polyorganosiloxane in the above range, appropriate peelability can be obtained between the formed ceramic green sheet.
[0049] (2-4) Catalyst The release agent composition in this embodiment preferably contains a catalyst from the viewpoint of efficiently proceeding with the above-mentioned condensation reaction by the melamine resin and from the viewpoint of promoting the ring-opening reaction of the epoxy resin. Examples of such catalysts are preferably acid catalysts, specifically, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, phosphorous acid, p-toluenesulfonic acid, etc., and particularly preferably p-toluenesulfonic acid.
[0050] The content of the catalyst in the release agent composition is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the total value of the melamine resin content and the epoxy resin content. The content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less.
[0051] (2-5) Other ingredients The release agent composition may contain, in addition to the above components, a crosslinking agent, a reaction inhibitor, an adhesion improver, a slipping agent, and the like.
[0052] (2-6) Properties of the release layer The thickness of the release agent layer is preferably 0.01 μm or more and 2 μm or less, more preferably 0.03 μm or more and 1 μm or less, and particularly preferably 0.1 μm or more and 0.5 μm or less, which provides good releasability and effectively prevents blocking when the release film is wound into a roll.
[0053] 2. Properties of release film for ceramic green sheet manufacturing process In the release film according to the present embodiment, the peeling force required for peeling the release film from the ceramic green sheet formed on the release surface can be appropriately set, but for example, it is preferably 10 mN / 40 mm or more, particularly preferably 15 mN / 40 mm or more, and more preferably 20 mN / 40 mm or more. In addition, the peeling force is preferably, for example, 300 mN / 40 mm or less, particularly preferably 200 mN / 40 mm or less, and more preferably 100 mN / 40 mm or less. In the release film according to the present embodiment, the release agent layer is formed from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane, so that the release force can be easily set to the above-mentioned value. The details of the method for measuring the above-mentioned peeling force are as described in the test examples described later.
[0054] 3. Manufacturing method of release film for ceramic green sheet manufacturing process The method for producing the release film in this embodiment is not particularly limited as long as it includes forming a release layer from the release agent composition described above. For example, it is preferable to coat one side of a substrate with a coating liquid containing the release agent composition described above and an organic solvent as required, and then dry and heat the resulting coating film to harden the release agent composition to form a release agent layer, thereby obtaining a release film.
[0055] Specific examples of the coating method include gravure coating, bar coating, spray coating, spin coating, knife coating, roll coating, and die coating.
[0056] The organic solvent is not particularly limited, and various organic solvents can be used. For example, hydrocarbon compounds such as toluene, hexane, and heptane, as well as isopropyl alcohol, isobutyl alcohol, acetone, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, and mixtures thereof can be used. In particular, it is preferable to use a mixture of methyl ethyl ketone and isopropyl alcohol.
[0057] The release agent composition applied as described above is preferably thermally cured. In this case, the heating temperature is preferably 80° C. or higher, and more preferably 100° C. or higher. The heating temperature is preferably 170° C. or lower, and more preferably 160° C. or lower. The heating time in the case of thermal curing is preferably 30 seconds or longer, and more preferably 50 seconds or longer. The heating time is preferably 120 seconds or shorter, and more preferably 90 seconds or shorter.
[0058] 4. How to use release film for ceramic green sheet manufacturing process The release film in this embodiment is preferably used to produce a ceramic green sheet. In this case, first, a ceramic slurry containing a ceramic material such as barium titanate or titanium oxide is applied to the release surface of the release agent layer. The application can be performed, for example, by a slot die coating method or a doctor blade method.
[0059] Examples of the binder component contained in the ceramic slurry include butyral resins, acrylic resins, etc. Examples of the solvent contained in the ceramic slurry include organic solvents, aqueous solvents, etc.
[0060] After the slurry is applied to the release surface, the applied ceramic slurry is dried to form a ceramic green sheet. After the ceramic green sheet is formed, the ceramic green sheet is separated from the release film. At this time, in the release film of this embodiment, the release agent layer is formed from a release agent composition containing melamine resin, epoxy resin, and polyorganosiloxane, so that the release film has excellent releasability to the ceramic green sheet. Therefore, the ceramic green sheet can be peeled off with an appropriate peeling force without cracking, breaking, or the like.
[0061] Next, to obtain a multilayer ceramic product, a plurality of ceramic green sheets separated from the release film are laminated and pressed together. At this time, in the release film of this embodiment, the release agent layer is formed from a release agent composition containing melamine resin, epoxy resin, and polyorganosiloxane, so that the adhesive strength between the ceramic green sheets is high during the lamination process of the ceramic green sheets, and thus the positional deviation between the plurality of ceramic green sheets is suppressed. As a result, defects such as poor cutting, reduced positional accuracy of electrodes, and delamination after firing the laminate are suppressed, and the yield of the obtained multilayer ceramic product is improved.
[0062] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.
[0063] For example, another layer such as an antistatic layer may be provided on the surface of the substrate opposite to the release agent layer, or between the substrate and the release agent layer. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0065] Example 1 95 parts by mass (solid content equivalent, the same below) of methylated melamine resin (manufactured by Sanwa Chemical Co., Ltd., product name "MW-30MLF", weight average molecular weight: 714) as the melamine resin, 5 parts by mass of rubber-modified epoxy resin (E1; manufactured by DIC Corporation, product name "TSR-601", epoxy equivalent: 450 to 500 g / eq, weight average molecular weight (Mw) 16,000) as the epoxy resin, 30 parts by mass of polyester-modified hydroxyl group-containing polydimethylsiloxane (manufactured by BYK Japan, product name "BYK-370", weight average molecular weight (Mw) 3,600) as the polyorganosiloxane, and 2 parts by mass of p-toluenesulfonic acid as the catalyst were mixed in a mixed solvent of isopropyl alcohol and methyl ethyl ketone (mass ratio 5:5) to obtain a coating solution of a release agent composition with a solid content of 3% by mass.
[0066] The obtained coating solution was uniformly applied onto one side of a biaxially oriented polyethylene terephthalate film (thickness: 38 μm) as a substrate using a bar coater. The obtained coating film was then dried and cured by heating at 150° C. for 1 minute to obtain a release film in which a release agent layer having a thickness of 0.1 μm was laminated on the substrate.
[0067] The thickness of the release agent layer was measured using a spectroscopic ellipsometer (manufactured by J.A. Woollam Japan, product name "M-2000").
[0068] [Examples 2 to 8] Release films were produced in the same manner as in Example 1, except that the type of epoxy resin was changed as shown in Table 1.
[0069] [Example 9, Comparative Example 1] Release films were produced in the same manner as in Example 1, except that the content of the melamine resin and the type and content of the epoxy resin were changed as shown in Table 1.
[0070] Comparative Example 2 100 parts by mass of an addition reaction type silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KS847H") and 1 part by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., product name "CAT-PL-50T") were mixed in a mixed solvent of toluene and methyl ethyl ketone (mass ratio 5:5) to obtain a coating solution of a release agent composition with a solid content of 2 mass%. Using the obtained coating solution of the release agent composition, a release film was produced in the same manner as in Example 1.
[0071] Details of the abbreviations and other information in Table 1 are as follows: <Epoxy resin> E1: Rubber-modified epoxy resin (DIC Corporation, product name "TSR-601", epoxy equivalent: 450-500g / eq, weight average molecular weight (Mw): 16,000) E2: Bisphenol F type epoxy resin / rubber modified epoxy resin = 70 / 30 (mass ratio) (DIC Corporation, product name "TSR-930", epoxy equivalent: 180-200g / eq, weight average molecular weight (Mw): 1,400) E3: Bisphenol A type epoxy resin / rubber modified epoxy resin = 70 / 30 (mass ratio) (DIC Corporation, product name "TSR-960", epoxy equivalent: 230-250g / eq, weight average molecular weight (Mw): 2,546) E4: Phenol novolac type epoxy resin (Mitsubishi Chemical Corporation, product name "jER-154", epoxy equivalent: 176-180g / eq, weight average molecular weight (Mw): 1,524) E5: Bisphenol A type epoxy resin (Mitsubishi Chemical Corporation, product name "jER-828", epoxy equivalent: 184-194g / eq, weight average molecular weight (Mw): 409) E6: Bisphenol F type epoxy resin (Mitsubishi Chemical Corporation, product name "jER-807", epoxy equivalent: 160-175g / eq, weight average molecular weight (Mw): 336) E7: Multifunctional epoxy resin (Mitsubishi Chemical Corporation, product name "jER-604", epoxy equivalent: 110-130g / eq, weight average molecular weight (Mw): 413) E8: Multifunctional epoxy resin (Mitsubishi Chemical Corporation, product name "jER-630", epoxy equivalent: 90-105g / eq, weight average molecular weight (Mw): 345)
[0072] [Test Example 1] (Evaluation of the peel strength between the release film and the green sheet) A ceramic slurry was prepared by adding 120 parts by mass of a mixture of toluene and ethanol (mass ratio 5:5) to 100 parts by mass of barium titanate (BaTiO3; manufactured by Sakai Chemical Industry Co., Ltd., product name "BT-03"), 10 parts by mass of a butyral-based binder resin (manufactured by Sekisui Chemical Co., Ltd., product name "BM-2"), and 5 parts by mass of dioctyl phthalate (manufactured by Kanto Chemical Co., Ltd., product name "Dioctyl Phthalate Grade 1"). The mixture was then mixed and dispersed in a ball mill.
[0073] The above ceramic slurry was uniformly applied to the release surface of the release agent layer of the release film that had been produced in the examples and comparative examples and stored at room temperature for 48 hours, and then dried in a dryer. As a result, a ceramic green sheet with a thickness of 3 μm was formed on the release film. The release film with the ceramic green sheet thus obtained was cut into a width of 40 mm, which was used as a measurement sample.
[0074] The substrate side of the measurement sample was fixed to a rigid plate, and the ceramic green sheet was peeled off from the release film at a peel angle of 90° and a peel speed of 0.3 m / min using a tensile tester (Shimadzu Corporation, product name "AG-IS500N"), and the force required for peeling (peel force; mN / 40 mm) was measured. The results are shown in Table 1.
[0075] [Test Example 2] (Evaluation of adhesive strength between green sheets) A ceramic green sheet having a thickness of 3 μm was formed on a release film in the same manner as in Test Example 1. The release film with the ceramic green sheet thus obtained was cut into a size of 100 mm length×100 mm width.
[0076] Next, an adhesive tape with a polyethylene terephthalate film as a base material was attached to the ceramic green sheet side of the release film with the ceramic green sheet, and the ceramic green sheet was supported so as to withstand the peel test. After peeling the release film from the release film with the ceramic green sheet, the ceramic green sheet side surface that had been in contact with the release surface of the release film was placed on the ceramic green sheet side surface of another release film with a ceramic green sheet, and the two ceramic green sheets were thermocompression bonded (60°C, 10 MPa). After that, the release film of the other release film with the ceramic green sheet was peeled off and cut into 10 mm squares, which were used as measurement samples.
[0077] The above measurement sample was fixed to a rigid plate, and the ceramic green sheets were peeled vertically at a peeling speed of 200 mm / min using a tensile tester (Shimadzu Corporation, product name "AG-IS500N") to measure the force required for peeling (adhesive strength: N / cm 2 The maximum value of was measured and the results are shown in Table 1.
[0078] [Test Example 3] (Measurement of surface free energy of release film) The contact angles of various liquid droplets on the release agent surface of the release films produced in the examples and comparative examples were measured. Based on the measured values, the surface free energy (mJ / m2 ) was obtained. The contact angle was measured using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DM-701") by the sessile drop method in accordance with JIS R3257:1999. For the droplets, diiodomethane was used as the "dispersion component", 1-bromonaphthalene as the "dipole component", and distilled water as the "hydrogen bond component". The results are shown in Table 1.
[0079] [Test Example 4] (Amount of silicone transferred to the green sheet surface) A ceramic green sheet having a thickness of 3 μm was formed on a release film in the same manner as in Test Example 1. The ceramic green sheet thus obtained was peeled off from the release film, and the silicon atom ratio (atomic %) was determined for the surface of the ceramic green sheet that had been in contact with the release film by X-ray photoelectron spectroscopy (XPS), which was used as an index of the amount of silicone transferred. The silicon atom ratio was calculated by determining the count numbers of each of the elements Si, C, O, Ti, and Ba, and taking the total amount as 100%, and the percentage of the count number of the Si element was taken as the silicon atom ratio (atomic %). The results are shown in Table 1.
[0080] [Table 1]
[0081] As can be understood from the above results, the release film of Comparative Example 2 using a general-purpose silicone-based release agent did not provide any adhesive strength between the ceramic green sheets. Also, the release film of Comparative Example 1, which does not contain an epoxy resin and uses only a melamine resin as the main component of the release agent composition, did not provide sufficient adhesive strength between the ceramic green sheets. In contrast, the release film of the Example, which uses a release agent composition containing an epoxy resin together with a melamine resin, provided a sufficiently high adhesive strength between the ceramic green sheets.
[0082] In general, the reason for the insufficient adhesive strength between ceramic green sheets is thought to be the migration of silicone-based components used in the release agent layer of the release film to the ceramic green sheet. However, when the amount of silicone migration to the green sheet surface on the side that was in contact with the release film was examined, the results showed that Comparative Example 1, which shows a value similar to that of the Examples, has poor adhesive strength between the green sheets. Therefore, the insufficient adhesive strength between the ceramic green sheets cannot be explained only by the migration of polyorganosiloxane. Therefore, it can be seen that the improvement in adhesive strength between the ceramic green sheets was achieved by forming the release agent layer of the release film that forms the ceramic green sheets from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane. [Industrial Applicability]
[0083] The release film for use in the ceramic green sheet manufacturing process of the present invention is suitable for forming ceramic green sheets for manufacturing laminated ceramic products.
Claims
1. A release film for a ceramic green sheet manufacturing process, comprising a substrate and a release agent layer provided on one side of the substrate, the release agent layer is formed from a release agent composition containing a melamine resin, an epoxy resin, and a polyorganosiloxane; The melamine resin is represented by the following general formula (a): 【Chemistry 1】 (In the formula, X represents -H, -CH 2 -OH, or -CH 2 -O-R, and may be the same or different. R represents an alkyl group having 1 to 8 carbon atoms, and may be the same or different. At least one X is -CH 2 -OH or -CH 2 -O-R.) or a polynuclear compound formed by condensing two or more of the above compounds, a mass ratio of the content of the melamine resin to the content of the epoxy resin in the release agent composition is 99:1 to 30:70; The content of the polyorganosiloxane in the release agent composition is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the total value of the content of the melamine resin and the content of the epoxy resin. A release film for use in a ceramic green sheet manufacturing process.
2. 2. The release film for use in the production process of a ceramic green sheet according to claim 1, wherein the polyorganosiloxane has at least one hydroxyl group in one molecule.
3. 3. The release film for use in a ceramic green sheet production process according to claim 1, wherein the polyorganosiloxane has a weight average molecular weight of 500 or more and 10,000 or less.
4. 4. The release film for use in a ceramic green sheet production process according to claim 1, wherein the melamine resin has a weight average molecular weight of 100 or more and 1,000 or less.
5. 5. The release film for use in a ceramic green sheet production process according to claim 1, wherein the release agent composition contains a catalyst.
Citation Information
Patent Citations
Release film for ceramic green sheet manufacturing process
JP2017105092A
Release film for ceramic green sheet production process and method for producing the same
JP2017144636A
Release film for producing ceramic green sheet
JP2019073003A
Method for removing functional layer from base film having functional layer, and method for collecting base film
JP2020090094A
Release film for green sheet manufacturing, release film manufacturing method for green sheet manufacturing, green sheet manufacturing method, and green sheet
WO2015129779A1